2023
DOI: 10.3389/fimmu.2022.1069207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the flame retardant 2,2’4,4’-tetrabromodiphenyl ether (PBDE-47) in THP-1 macrophage-like cell function via small extracellular vesicles

Abstract: 2,2’4,4’-tetrabromodiphenyl ether (PBDE-47) is one of the most widespread environmental brominated flame-retardant congeners which has also been detected in animal and human tissues. Several studies have reported the effects of PBDEs on different health issues, including neurobehavioral and developmental disorders, reproductive health, and alterations of thyroid function. Much less is known about its immunotoxicity. The aim of our study was to investigate the effects that treatment of THP-1 macrophage-like cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Studies performed on the Boston Birth Cohort provided evidence that in utero exposure to PBDEs may epigenetically reprogramme the offspring's immunological response through promoter methylation of a proinflammatory gene [203]. These data agree with the in vitro results using macrophage-like cell lines, where cytokine production and miRNA expression were modulated by BDE-47 treatment [97][98][99].…”
Section: Developmental Immunotoxicologysupporting
confidence: 79%
See 1 more Smart Citation
“…Studies performed on the Boston Birth Cohort provided evidence that in utero exposure to PBDEs may epigenetically reprogramme the offspring's immunological response through promoter methylation of a proinflammatory gene [203]. These data agree with the in vitro results using macrophage-like cell lines, where cytokine production and miRNA expression were modulated by BDE-47 treatment [97][98][99].…”
Section: Developmental Immunotoxicologysupporting
confidence: 79%
“…Furthermore, they demonstrated that BDE-47 treatment can regulate the sEVs' cargo with purposeful consequences toward downstream events and target bystander macrophages. Exacerbating the macrophage LPS-induced pro-inflammatory response [99] as well as altering A549 epithelial lung cells which modulate mRNA expression of tight junctions, adhesion molecules, cytokines and EMT (epithelial-mesenchymal transition) markers [100]. Finally, it has been shown that BDE-47 can also induce cardiovascular toxicity, activating PPARγ in THP-1 monocytes, inducing the foam cell formation typical of a proatherogenic process [101].…”
Section: Polybrominated Diphenyl Ethers (Pbdes)mentioning
confidence: 99%
“…Recently, research on the impact of polybrominated diphenyl ethers (PBDEs), a widespread environmental pollutant, on EVs has been extensively investigated. For instance, BDE-47 has been found to modulate small EV (sEV) biogenesis and their miRNA cargo, exacerbating the lipopolysaccharide (LPS)-induced pro-inflammatory response in THP-1 macrophages [133,134]. Purified sEVs from BDE-47-treated THP-1 macrophages may affect the expression of surface markers in a naïve resting M(0) macrophage cell line, impairing the ability to make immunological synapses and present antigens downregulating the expression of HLA-DR and CD209 antigens [133].…”
Section: The Impact Of Pollution On Extracellular Vesicle (Ev) Biogen...mentioning
confidence: 99%
“…Persistent exposure to PBDE-47 can impair innate immunity in mammary tissue [280]. PBDE-47 can disrupt the secretion of proinflammatory cytokines (IL-6 and TNF-α) and interfere with basophil activation [281][282][283][284]. Peripheral blood mononuclear cells (PBMC) from subjects who had autism spectrum disorders (ASD) showed a higher response to lipopolysaccharide (LPS) when pretreated with PBDE-47 compared with the control group [285].…”
Section: Inflammatory Responsementioning
confidence: 99%